Current Status of Stone-Cutting Waste Management in Palestine. - Rahaf Ghozzi; Bara’a Abu Baker; Abdelraheem khateeb; Saad Jodallah (My University, 2022)
Stone and marble sector is one of the most important industries worldwide. its annual sales reach about 10% of the global market. Palestinian stone takes 4% of global. Palestinian stone is exported to more than 80 countries, it represents about 4.5 percent of Palestinian GDP and employs 20,000 workers directly and 100,000 workers indirectly in about 1200 facilities. However, the stone and marble industry in Palestine suffers from a high present of stone waste produced, while adopting inadequate methods dealing with this waste. Moreover, there are clear negative impacts of this waste on both the environment and human health, hence this industry weakly complies with sustainability standards. Also, in this project the effect of waste management on the organization's performance was investigated from the point of view of factory owners. The goal of this project is to assess the current local stone-waste management practices. During the project a comprehensive literature review was conducted on previously published work about Palestinian stone, local stone waste management practice, global best practices in dealing with stone waste, and about standard waste management models. Furthermore, a questionnaire was developed to collect quantitative and qualitative data. Finally, based on data collected from 53 factories, it appears that the final product has 52.18 percent raw stone input and 47.82 percent waste of production. Furthermore, annual solid waste amounts to an average of 1901.38 tons, or 26.49 percent of raw stone. On the other side, annual liquid waste amounts to 1736.77m3, or 86.99 percent of total input water (of course liquid waste includes fine powder as well). In addition, the majority of factories dispose of solid waste in crushers and treat liquid waste in purification plants and silos, according to the data. While factories who don’t treat the liquid waste, most of them get rid of the liquid waste in random landfill. For sludge, most of factories don’t use it, and dispose it in dedicated landfill.